2007
DOI: 10.1016/j.appdev.2007.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood anxious solitude and subsequent peer relationships: Maternal and cognitive moderators

Abstract: It was hypothesized that the relation between early anxious solitude and subsequent peer relation would be moderated by early relational (maternal sensitivity) and individual factors (child school readiness). Participants were 1,364 children from the National Institute of Child Health and Human Development's Study of Early Child Care and Youth Development. Anxious solitude was assessed by child care providers from 2 to 4.5 years, maternal sensitivity was observed during mother-child interactions from 2 to 4.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…These results add to the growing number of recent studies that have identified risk and protective factors in the adjustment developmental pathways of shy children, including parental characteristics , friendships (Rubin et al, 2006), and classroom climate (Gazelle & Spangler, 2007). Moreover, these findings extend the small body of literature suggesting that language skills may serve a protective role for shy children (e.g.…”
Section: Pragmatic Language As a 'Buffer'supporting
confidence: 64%
“…These results add to the growing number of recent studies that have identified risk and protective factors in the adjustment developmental pathways of shy children, including parental characteristics , friendships (Rubin et al, 2006), and classroom climate (Gazelle & Spangler, 2007). Moreover, these findings extend the small body of literature suggesting that language skills may serve a protective role for shy children (e.g.…”
Section: Pragmatic Language As a 'Buffer'supporting
confidence: 64%
“…For instance, Blair and colleagues (2004) found a positive relation between maternal ratings of inhibited behavior and assessments of cognitive regulation measures. Furthermore, Coplan and colleagues (2001) reported an association between observed shy/withdrawn behavior and academic achievement for girls, and Gazelle and Spangler (2007) have reported similar findings for boys.…”
Section: Discussionmentioning
confidence: 65%
“…For instance, some children with social anxiety enjoy relatively positive peer relations, whereas others are victimized and excluded by peers (Gazelle, 2008; Greenberg & Kusche, 2006). Such differences appear to be the product of diverse influences, including the quality of early parental relations (Gazelle & Spangler, 2007) and the emotional climate of the concurrent classroom environment (Gazelle, 2006). Moreover, different peer experiences may place socially anxious children on diverse emotional trajectories over time (Gazelle & Ladd, 2003; Gazelle & Rudolph, 2004).…”
Section: Controversiesmentioning
confidence: 99%